2001
DOI: 10.1007/3-540-45271-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Active Query Caching for Database Web Servers

Abstract: Abstract.A substantial portion of web traffic consists of queries to database web servers. Unfortunately, a common technique to improve web scalability, proxy caching, is ineffective for database web servers because existing web proxy servers cannot cache queries. To address this problem, we modify a recently proposed enhanced proxy server, called an active proxy, to enable Active Query Caching. Our approach works by having the server send the proxy a query applet, which can process simple queries at the proxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Finally, our work complements recent research on various active proxy caching techniques, some of which do not specifically address database queries ( [3], [5]), and some address database queries but not function-embedded queries ( [1], [12], [13], [14]). …”
Section: Related Workmentioning
confidence: 83%
See 1 more Smart Citation
“…Finally, our work complements recent research on various active proxy caching techniques, some of which do not specifically address database queries ( [3], [5]), and some address database queries but not function-embedded queries ( [1], [12], [13], [14]). …”
Section: Related Workmentioning
confidence: 83%
“…With the proliferating use of the Web, certain types of databasebacked web sites also heavily utilize user-defined functions in answering user queries. While recent research ( [1], [13], [14]) has shown the usefulness of advanced web proxy caching for general database-backed web sites, their techniques are not directly applicable to web sites with function-embedded queries, which are queries with embedded calls to use-defined functions. Our goal in this paper is to explore proxycaching techniques for these function-embedded queries.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies did not consider database queries. Our previous work [26] focused on how a custom proxy caching protocol could be used to distribute caching code for select-project-join queries to proxies on the fly. However, it did not study the main issues we focus here, including how forms can be used in the definition and deployment of caching schemes, and how well these schemes perform for keyword-based or function-embedded queries over the web.…”
Section: Related Workmentioning
confidence: 99%
“…3 However, DICE can produce remainder queries for the complete and exact missing results to a given query, while their work uses heuristics to provide approximate answers to user queries. Furthermore, whereas Luo and Naughton process only simple conjunctive queries, DICE can also handle queries with predicates connected by AND and OR and that might include a constant number of joins and comparison predicate values.…”
Section: Seeds Of Internet Growthmentioning
confidence: 99%
“…3,4 All queries that DICE handles refer to the same set of data sources, which greatly simplifies the process of answering queries using the cached views. Unlike some related applications, 5-7 the class of applications supported by our data-integration infrastructure requires no complex, generalized algorithms to solve the problem of query containment (known to be NP-complete).…”
Section: Deployment Issuesmentioning
confidence: 99%